2021
DOI: 10.4314/njbas.v28i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Biofilm Producing Methicillin-Resistant Staphylococcus aureus from Hospitalized Orthopaedic Patients in Kano State, Nigeria

Abstract: Biofilm formation and resistance to methicillin are among the factors that makes Staphylococcus aureus a very important human pathogen in both health-care and community settings. This study investigated methicillin-resistance among biofilm-producing S. aureus isolated from 49 orthopaedic in-patients within a 3 months period. Wound swabs, nasal swabs, bed swabs and urine samples were collected from each patient. The samples were cultured and screened for presence of S. aureus while the micro-titre plate method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Even though S. aureus is a normal flora of the skin, the prevalence of S. aureus in this study is significantly high for a hospital setting despite the aseptic measures put in place during hospital procedures. The frequency in which S. aureus was isolated in this study is more than 14.8% reported by Oche et al [20]. Using oxacillinresistance screening agar (ORSA), this study had an MRSA prevalence of 31 (70.5%).…”
Section: Discussionmentioning
confidence: 52%
“…Even though S. aureus is a normal flora of the skin, the prevalence of S. aureus in this study is significantly high for a hospital setting despite the aseptic measures put in place during hospital procedures. The frequency in which S. aureus was isolated in this study is more than 14.8% reported by Oche et al [20]. Using oxacillinresistance screening agar (ORSA), this study had an MRSA prevalence of 31 (70.5%).…”
Section: Discussionmentioning
confidence: 52%
“…"Occurrence of biofilm forming strain reported in this study could be linked to the slow progression in wound healing process among orthopaedic patients. The biofilm matrix is known to be a vital factor in preventing antibiotics from reaching the infecting organisms within the matrix" [38], thereby conferring resistance on the bacteria within the biofilm matrix. Biofilm forming MRSA was identified consisting of high proportion 21.8%frompost-surgical wound followed by fracture wound sample recording 11.6%.…”
Section: Table 3 Multidrug Resistant (Mdr) Index Of Biofilm-forming M...mentioning
confidence: 99%
“…In this study, the Spearman's Rho Correlation statistical tool showed association between MRSA production and biofilm formation to be statistically significant at p< .05. This may be a sign that "due to the proximity or adherence of bacteria (MRSA) cells to each other within biofilms, resistant genes that confer resistance such as the mecAgene are easily transferred from one cell to other cells through HGT, thereby making the whole biofilm community resistant to methicillin and other antibiotics" [38].…”
Section: Table 3 Multidrug Resistant (Mdr) Index Of Biofilm-forming M...mentioning
confidence: 99%